A formação de redes sociais eletrônicas e o papel estruturante do software livre de código aberto: o caso da Fundação Telefônica - Santaliestra, Rodrigo (2007)
This work presents a study about the creation of electronic social networks and the structuring role of Open Source and Free Software (OS/FS), from the experience of the Rede de Atenção à Criança e ao Adolescente (Child and Teenage Support Network) of the Pró-Menino Program from the Telefônica Foundation. It was necessary to walk through different branches of knowledge in order to understand the various aspects of electronic social networks, and, from there, build a multifaceted view of the problem. This trajectory was built along ten months of work, with eight cities in the State of São Paulo and with the Telefônica Foundation, until the creation of a software, starting from the following questions: 'what will be considered a successful electronic network software for these cities?' and 'what makes a software like this have long-term success?'. The work enabled the understanding of how OS/FS can assist social networks and the learning it may make available, showing that gratuity is only one of its characteristics. OS/FS has a series of aspects that may constitute structuring elements of the network, be it in respect to software production models, be it in managing project teams with high technical complexity on geographically scattered communities with no hierarchic control and, finally, with respect to the aspects of production and distribution of knowledge as public goods.